2018
DOI: 10.20944/preprints201807.0426.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ginsenoside Rh2 Ameliorates Lipopolysaccharide Induced Acute Lung Injury by Regulating the TLR4/ PI3K/Akt/mTOR, Raf-1/MEK/ERK and Keap1/Nrf2/HO-1 Signaling Pathways in Mice

Abstract: The anti-inflammatory effect of ginsenoside Rh2 (GRh2) is one of the most important ginsenosides. The purpose of this study is to identify the anti-inflammatory and antioxidant effects of GRh2 after LPS challenge lung injury animal model. GRh2 reduced LPS-induced NO, TNF-α, IL-1, IL-4, IL-6 and IL-10 productions in lung tissues. GRh2 treatment decreased the histological alterations in the lung tissues and BALF protein content and total cells number also diminished in LPS-induced lung injury mice. Mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 3 publications
1
25
0
Order By: Relevance
“…In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42]. In a recent study, the authors showed that NRF2 is a repressor of NF-κB [43].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42]. In a recent study, the authors showed that NRF2 is a repressor of NF-κB [43].…”
Section: Discussionsupporting
confidence: 92%
“…Because exposure to IL-4, IL-10, or glucocorticoids could induce a type of M2-polarized macrophage [51,52], the previously reported induction of anti-inflammatory cytokine IL-10 by ginsenosides Rg6, Rb1, Rc, Rd, Re, Rf, Rg1, Rh1, Rh2, and Rp1, as well as compound K [14,23,24,41,[61][62][63][64][65][66][67], or activation of glucocorticoid receptors by compound K, ginsenosides Rg1, and Re [36][37][38][39] may imply that those ginsenosides could partly induce the resolution of inflammation through M2 polarization.…”
Section: Perspectivementioning
confidence: 99%
“…HO‐1 is a stress‐regulated protein induced by Nrf2 protects against the cytotoxicity of various oxidative stresses response. Nrf2 as a signaling protein can up‐regulate antioxidant enzymes, thereby reducing oxidative stress caused by ROS 11,34,35 . Moreover, previous study displayed that cisplatin damaged anti‐oxidant defense mechanisms followed by an apparent reduce in GSH and increase in MDA levels.…”
Section: Discussionmentioning
confidence: 98%